PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI ISSI PERIODE 2020-2024 - Nuraniza Hanum; Faturahman Faturahman (Prodi Akuntansi Syariah UIN Sulthan Thaha Saifuddin Jambi, 2026)
This research is motivated by the fact that in the food and beverage sub-sector there is a discrepancy between theory and the data found as well as inconsistencies in research results from previous studies. Therefore, this research aims to determine the effect of Return on Equity, Quick Ratio and Debt to Asset Ratio on profit growth in food and beverage sub-sector companies registered with ISSI for the 2020-2024 period. This research uses secondary data originating from the BEI website in the form of Financial Reports. This research method uses quantitative methods and the analytical methods used are descriptive statistical tests, classical assumption tests, panel data analysis and hypothesis testing (T-Test and F-Test) using the Eviews 12 program. The population in this research is all food and beverage sub-sector companies registered with ISSI for the 2020-2024 period, namely 75 companies and the sampling technique in this research uses the Purposive Sampling technique so that 9 companies are obtained. The results of this research show that the variable Return on Equity (X1) partially has a positive and significant effect on profit growth. The Quick Ratio (X2) variable partially has a positive and significant effect on profit growth. And the variable Debt to Asset Ratio (X3) partially has a positive and significant effect on profit growth. Simultaneously Return on Equity, Quick Ratio and Debt to Asset Ratio influence profit growth.